Computational insights into the interaction mechanism of transcription cofactor vestigial-like protein 4 binding to TEA domain transcription factor 4 by molecular dynamics simulation and molecular mechanics generalized Born/surface area) calculation. Issue 10 (3rd July 2019) - Gao, Jian; Zhang, Yiran; Chen, Han; Chen, Qingqing; Feng, Dingding; Zhang, Ling; Li, Chenglin
Abstract: Hippo pathway has been implicated in the suppression of tissue overgrowth and tumor formation by restricting the oncogenic activity of Yes-associated protein (YAP). Transcription cofactor vestigial-like protein 4 (VGLL4), a natural YAP antagonist that competes with YAP for TEA domain transcription factor 4 (TEAD4) binding is a potential tumor suppressor in human gastric cancer. Comparing with the full length of VGLL4, the Tondu 2 domain of VGLL4 alone is fully functional in inhibiting YAP-induced TEAD4 reporter activity. Revealing the details of binding interaction between VGLL4 and TEAD4 would accelerate the discovery of improved drugs against YAP-driven human cancers. We investigated systematically the interaction mechanisms between TEAD4 and VGLL4 by molecular dynamics (MD) simulation, free energy calculation, and free energy decomposition analysis. Our simulations show that two loops of VGLL4 (residues 218–222 and 251–252) have little binding contribution on VGLL4 binding to TEAD4. The β1 strand of VGLL4 plays important role in the contribution to the binding, whereas the α3 helix gives small contribution. More interestingly, the mutation of several residues of α2 helix to alanine results in the contribution of α2 helix decreasing, accompanied by the increased binding contribution of α3 helix. Deletion of the β1 or α3 segment of VGLL4 has slight effect on the remaining two segments. Our simulation is well consistent with the in vivo evaluation of the binding of biotinylated VGLL4 peptides to TEAD4 in HepG2 cells by immunological approaches. We expect this work can provide valuable information for design of improved VGLL4 derivative anticancer peptides. Communicated by Ramaswamy H. Sarma